2020
DOI: 10.29103/averrous.v6i1.2663
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Perilaku Merokok Mahasiswa Universitas Malikussaleh 2019

Abstract: Konsumsi rokok dikalangan remaja dan mahasiswa meningkat setiap tahunnya. Data The Tobacco Atlas menyebutkan Indonesia memiliki jumlah perokok remaja pria terbesar (66%). Penelitian ini bertujuan untuk mengidentifikasi karakteristik serta faktor yang mempengaruhi perilaku merokok pada mahasiswa pria di Universitas Malikussaleh. Penelitian ini merupakan studi deskriptif dengan desain cross sectional. Teknik pengambilan sampel menggunakan quota sampling dengan jumlah sampel 192 orang yang telah memenuhi kriteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The majority of respondents in this study fell into the light smoker category (80.4%). It is in line with research by Sawitri et al [30], which concluded that the majority of students who smoke are light smokers, and most are aged 20-24 years. Based on gender, men constituted the largest number of smoking respondents (86.3%).…”
Section: Resultssupporting
confidence: 92%
“…The majority of respondents in this study fell into the light smoker category (80.4%). It is in line with research by Sawitri et al [30], which concluded that the majority of students who smoke are light smokers, and most are aged 20-24 years. Based on gender, men constituted the largest number of smoking respondents (86.3%).…”
Section: Resultssupporting
confidence: 92%
“…15 In this study, it was found that the age group of 22-23 years was the largest group with a total of 26 respondents, which following the research by Sawitri et al 2020, which states that the age of 20-24 years is the age of students with the maturity to make their own pleasure decisions. 19 The results of the cross-table of smoking habits on sleep quality show the category of light smoking habits with a variety of good sleep quality, with as many as 23 respondents. Many factors can influence this, one of which is that many teenagers follow their friends, experimenting, wanting to feel/curious and lonely, looking stylish, a symbol of maturity, as a stress reliever, and the last is imitating parents.…”
Section: Discussionmentioning
confidence: 99%
“…The Global Youth Tobacco Survey (GYTS) stated that Indonesia is the country with the highest number of teenage smokers in the world and the age at which they first tried smoking based on age group and sex based on the 2014 GYTS men who first smoked at the age of 12-13 years, and most women first tried smoking at the age of 14-15 years (Sawitri & Maulina, 2020;RI Ministry of Health, 2015).…”
Section: Introductionmentioning
confidence: 99%